Survival Analysis of Lymphoepithelioma-Like Carcinoma of the Urinary Bladder and the Effect of Surgical Treatment Modalities on Prognosis - Wu, Jie; Shou, Jian-Zhong; Wang, Yu-Chen (Frontiers in Surgery, 2021)
Purpose This study aimed to investigate the prognostic factors of patients with lymphoepithelioma-like carcinoma of the urinary bladder (LELCB) and to explore the value of surgical treatment. Methods Date of patients with LELCB were extracted from the Surveillance, Epidemiology, and End Results (SEER) database. Multivariate analysis was performed using the stepwise Cox proportional hazards regression model and conditional inference tree method to identify significant prognosticators of overall survival (OS) from the following parameters: age, gender, lymph node involvement, tumor extent, radiation, chemotherapy and surgery type. Literature review (LR) was performed, and eligible cases were used to validate prognostic classification using the Kaplan-Meier method with log-rank tests. Results Sixty patients with a median age of 69.5 years were identified from the SEER database and 91 patients through LR. The Cox analysis identified age, gender, lymph node involvement, and surgical approach as independent prognosticators of OS. Based on the nomogram scores, patients were stratified into three prognostic groups: (I) patients younger than 70 years; (II) patients older than 70 years, who received bladder-sparing therapy (BST); and (III) patients older than 70 years undergoing radical cystectomy (RC). Patients in group II had the worst outcomes in terms of OS compared with patients in group I and III (p < 0.001 and p = 0.03, respectively). A similar survival pattern was found in the LR cohort. Conclusion The nomogram provided individualized prognostic quantification of OS in patients with LELCB. BST could yield favorable outcomes when treating LELCB, especially for younger patients, while older patients might derive more survival benefit from RC.